2012
DOI: 10.1007/s11356-012-0887-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific modulation of immune system complement gene expression in marine medaka Oryzias melastigma following dietary exposure of BDE-47

Abstract: BDE-47 is one of the most widely found congeners of PBDEs in marine environments. The potential immunomodulatory effects of BDE-47 on fish complement system were studied using the marine medaka Oryzias melastigma as a model fish. Three-month-old O. melastigma were subjected to short-term (5 days) and long-term (21 days) exposure to two concentrations of BDE-47 (low dose at 290 ± 172 ng/day; high dose at 580 ± 344 ng/day) via dietary uptake of BDE-47 encapsulated in Artemia nauplii. Body burdens of BDE-47 and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 41 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…For instance, observed that exposure of rainbow trout to municipal sewage treatment effluents resulted in decreased antibody production and reduced lymphocyte number in sexually mature females but not in males. Similarly, Ye et al (2012) found sexspecific differences in the response of the complement system of the marine medaka (Oryzias melastigma) exposed to a polybrominated flame retardant. These examples show that the fact that 79% of the published immunotoxicity studies do not provide information on the sex of the experimental fish, represents a serious information gap.…”
Section: Main Groups Parametersmentioning
confidence: 85%
“…For instance, observed that exposure of rainbow trout to municipal sewage treatment effluents resulted in decreased antibody production and reduced lymphocyte number in sexually mature females but not in males. Similarly, Ye et al (2012) found sexspecific differences in the response of the complement system of the marine medaka (Oryzias melastigma) exposed to a polybrominated flame retardant. These examples show that the fact that 79% of the published immunotoxicity studies do not provide information on the sex of the experimental fish, represents a serious information gap.…”
Section: Main Groups Parametersmentioning
confidence: 85%
“…Moreover, the BDE-47-stimulated increased mRNA levels of IL-6 and IL-8, suggesting that activation of transcription contributes to the overall increased cytokine expression. Because the fold change in cytokine protein production was modest compared to the fold change in cytokine mRNA expression, additional post-transcriptional mechanisms may modulate protein expression (Griesinger et al , 2001; Wang et al , 2011; Ye et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The marine medaka Oryzias melastigma ( O. melastigma ) is an emerging marine fish model used in the investigation of the response of organisms to pollutants, toxins and stresses in marine environments [ 5 , 6 ]. In fact, O. melastigma is already used in a variety of estuarine and marine ecotoxicological studies [ 7 - 10 ], demonstrating their potential in studying the effect of organic chemicals, inorganic chemicals, microorganism and environmental stresses in relation to cardiac toxicity [ 11 ], hepatotoxicity [ 9 ], neurotoxcity [ 12 ], immunotoxicity [ 10 ], and so forth. In addition, O. melastigma has been adopted by the International Life Sciences Institute (ILSI) Health and Environmental Science Institute (HESI) for embryo toxicity testing.…”
Section: Introductionmentioning
confidence: 99%